PENERAPAN DIGITAL MARKETING DALAM BUDIDAYA LELE DENGAN SISTEM SAUNA DI KARANG TARUNA TEKAD MANDIRI UNIT 5 SENDANGSARI MINGGIR SLEMAN DAERAH ISTIMEWA YOGYAKARTA - Kuswanto Kuswanto; Khori Najib; Muhammad Isnaini Fathoni; Ary Subiyantoro; Subandi Subandi (HIKMAYO: JURNAL PENGABDIAN MASYARAKAT AMAYO, 2022)
People who have businesses should have expertise and knowledge in handling theirbusinesses, so they can develop their businesses easily without any problems. The purposeof this community service activity is to stabilize the state of agriculture to livestock. Withcultivation, breeders also indirectly create new jobs for the residents around thiscommunity service activity which is followed by community members. This activityinvolved a team of AMA Yogyakarta lecturers in an effort to collaborate with thecommunity in order to develop their business. Based on the data on the results of the fieldservice that the author carried out, that by holding this service the community has theability to develop the business they already have.